2022
DOI: 10.1093/aje/kwac194
|View full text |Cite
|
Sign up to set email alerts
|

Are We Undercounting the True Burden of Mortality Related to Suicide, Alcohol Use, or Drug Use? An Analysis Using Death Certificate Data From Colorado Veterans

Abstract: Knowledge regarding deaths due to suicide, alcohol-related, or drug-related causes may be limited by inconsistent and/or restrictive case definitions, resulting in concerns regarding validity of findings and underestimates of burden. In this proof-of-concept study, we assessed varying case definitions (suicide, alcohol-related, drug-related mortality using underlying cause of death [UCOD] versus multiple cause of death [MCOD]) based on counts and rates among Colorado Veterans who died (2009-2020). Suicide, alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Drug-related mortality increased steeply beginning in the late 1990s, continuing to rise to the highest rates ever observed in 2021. In contrast, suicide mortality, also highlighted by Spark et al (1), increased slowly across the late 1990s and early 2000s, with more rapid increases beginning in 2006 (5).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Drug-related mortality increased steeply beginning in the late 1990s, continuing to rise to the highest rates ever observed in 2021. In contrast, suicide mortality, also highlighted by Spark et al (1), increased slowly across the late 1990s and early 2000s, with more rapid increases beginning in 2006 (5).…”
mentioning
confidence: 97%
“…Despite evidence that these three causes of death do not trend together, research in both the U.S. and worldwide continues to analyze these causes together (e.g., ( 9)). While Spark et al (1) do not explicitly use the term "deaths of despair," their work perpetuates the concept by analyzing the three underlying causes of death -suicide, drug-and alcohol-related -and arguing for an expanded and consistent case definition for the three causes. While perhaps unintentional, their analysis highlights a need to move beyond a crude conceptualization of these causes of death as representing the same underlying phenomenon with the same underlying drivers.…”
mentioning
confidence: 99%
“…40 Irrespective of criteria used (i.e., ICD, DSM , self-report), AUD is underdiagnosed. 37 , 41 , 42 Henceforth in this review, “AUD” refers to diagnoses made via any version of ICD or DSM criteria; otherwise, levels and frequency of alcohol consumption are indicated.…”
Section: Results Of the Reviewed Studiesmentioning
confidence: 99%
“…This may represent more opportunity to diagnose, intervene, and prevent mortality in the mTBI+ group. Examining cause(s) of death, especially drug- and alcohol-related, could provide additional information on adverse events not captured by VHA data 33. For example, a review of drug overdose mortality based on VHA use (yes/no; defined as having a VHA encounter in the calendar year or the prior year) found that, in 2019, non-VHA using veterans had a higher number of overall drug overdose deaths and opioid overdose deaths compared with veterans using VHA care 34.…”
Section: Resultsmentioning
confidence: 99%
“…Examining cause(s) of death, especially drug-and alcohol-related, could provide additional information on adverse events not captured by VHA data. 33 For example, a review of drug overdose mortality based on VHA use (yes/no; defined as having a VHA encounter in the calendar year or the prior year) found that, in 2019, non-VHA using veterans had a higher number of overall drug overdose deaths and opioid overdose deaths compared with veterans using VHA care. 34 In our cohort, higher OUD and mortality among the no CTBIE group may suggest a higher risk of OUD/overdose-related death.…”
Section: Discussionmentioning
confidence: 99%